The Correlation Between Students Learning Style and Reading Comprehension: A Quantitative Study - Annisa Nurul Baeti; Rizka Zahra Amalia; Robby Slamet; Siti Salamah Fauziyah; Silmy Kaaffah Nurshiha, (Journal of Applied Linguistics (ALTICS), 2024)
This study aims to investigate the correlation between learning style and reading comprehension among undergraduate students majoring in English Education at one of the universities in Indonesia. This study applied quantitative research with correlational study of variables to determine the existence of a possible relationship between two variables. This study was implemented on twenty graduate students. Questionnaires were used to gather the data to identify students learning styles and reading comprehension. The result shows no significant correlation between the two variables, concluding that individual learning preferences may exist, but they do not influence students' reading comprehension skills. Keywords: Learning style, reading comprehension, correlation.